Prognostic value of thyroid-stimulating hormone within reference range in patients with coronary artery disease - Ndrepepa, Gjin; Braun, Siegmund; Mayer, Katharina; Cassese, Salvatore; Fusaro, Massimiliano; Byrne, Robert A.; Hoppmann, Petra; Schunkert, Heribert; Laugwitz, Karl-Ludwig; Kastrati, Adnan (Metabolism-Clinical and Experimental, 2015)
Background Thyroid-stimulating hormone (TSH) in the upper part of reference range is associated with cardio-metabolic disorders. The association of TSH within reference range with prognosis of patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI) remains poorly investigated. Methods The study included 8010 consecutive patients with CAD who were treated with PCI. All patients had a TSH level within reference range (0.3 to 4.0 mU/L). The primary outcome was 3-year all-cause mortality. Results TSH tertiles were: 1st tertile (0.3 mU/L to < 1.02 mU/L; n = 2694), 2nd tertile (1.02 mU/L to < 1.67 mU/L; n = 2654) and 3rd tertile (1.67 mU/L to 4.00 mU/L; n = 2662). The primary outcome (3-year mortality) occurred in 753 patients: 240 deaths in the 1st, 227 deaths in the 2nd and 286 deaths in the 3rd TSH tertile (Kaplan-Meier estimates of mortality 10.2%, 9.8% and 12.3%; adjusted hazard ratio [HR] = 1.31, 95% confidence interval [CI] 1.04-1.66 for each tertile increase). TSH level was associated with 30-day mortality (mortality estimates, 1.6% in the 1st, 1.6% in the 2nd and 3.5% in the 3rd TSH tertile; adjusted HR = 2.30 [1.33-3.97] for each tertile increase) but not with 30-day to 3-year mortality (mortality estimates, 8.6% in the 1st, 8.2% in the 2nd and 8.8% in the 3rd TSH tertile; P = 0.603). The incidence of cardiogenic shock or peri-PCI bleeding was increased in patients in the upper TSH tertile. Conclusion In patients with CAD undergoing PCI, TSH level in the upper part of reference range was associated with increased risk of mortality after PCI.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary artery disease; Mortality; Thyroid-stimulating hormone